Application of The Accounting Information System as A Conductive Climate Enhancement to Develop MSME in Bungah District - Kurnia Cahya Lestari; Moh. Ririn Rosyidi (Universitas PGRI Madiun, 2020)
ABSTRACTThis study aims to evaluate the application of Accounting Information Systems that have been used by UD. ModeX, MSME in Bungah District so that MSMEs can produce as financial statements. Good financial statements help MMSME to propose additional funds for developing the business to financial institutions, consideration in making decisions so that MSMEs businesses work effectively and efficiently. The study was conducted by direct interviews with the owner, specialized staff, and the cashier at UD. ModeX. The results of the research, by applying the Accounting Information System application are facilitating the recording of financial transactions, seeing the stock of goods quickly and accurately. Moreover, from the accounting information formed a financial report, MSMEs has a financial statement to use for the various business benefit of the MSME.ABSTRAKPenelitian ini bertujuan untuk mengevaluasi penerapan aplikasi Sistem Informasi Akuntansi yang telah digunakan oleh UD. ModeX, UMKM yang berada di Kecamatan Bungah agar dapat digunakan sebagai penyusunan laporan keuangan. Penyusunan laporan keungan yang baik membantu UMKM dalam mengajukan permodalan kepada lembaga keuangan, pertimbangan dalam pengambilan keputusan sehingga bisnis UMKM berjalan secara efektif dan efesien. Penelitian dilakukan dengan wawancara langsung kepada owner, staff khusus, dan bagian kasir pada UD. ModeX. Hasil dari wawancara tersebut yaitu dengan menerapkan aplikasi Sistem Informasi Akuntansi dapat mempermudah pencatatan transaksi keuangan, melihat stok barang secara cepat dan akurat, dan dari informasi akuntansi tersebut terbentuk suatu laporan keuangan yang dapat digunakan untuk berbagai kepentingan kelancaran bisnis UMKM tersebut.